Arduino Based Security System for Women - K.VANISREE,; MUDE SREENIVASULA,; Y.JALAJAKSHI,, (International Journal of Psychosocial Rehabilitation, 2020)
Raped, molested, and abducted women are among the problems that women face. Fraud will be reduced as a result of the use of this strategy, which was developed exclusively for women. In order to safeguard women, especially in urban locations where they may have problems travelling, it has been emphasised. Because the device is not unreasonably expensive, many women have elected to utilise it instead of other options.might be beneficial to oneself